(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This research explores the spatial pattern and determinants of crime incidence in the urban neighborhoods of Katsina City, Nigeria. The objectives are to unravel the rate, frequency, and factors responsible for the crime occurrence in the selected neighborhoods of Katsina City. A purposive sampling technique was adopted to choose seven neighborhoods prone to crime in Katsina City. A total of 366 questionnaires were successfully administered using stratified sampling methods. Descriptive statistics and mean scores were used to analyse and interpret the data. The findings indicate a rising trend in crime in Katsina City, with theft (39.9%), drug peddling (20.6%), and criminal breach of trust and cheating (10.3%) being the most prevalent offenses. A high crime rate (57.6%) was observed. In addition, the frequency of the crime occurrences in the study area is predominantly daily or weekly (71.1%), suggesting that criminal activities are frequent in Katsina. There is a notable spatial variation in the occurrence and intensity of crime across the selected neighborhoods, and the Sabuwar Unguwa community accounts for more than one-third (34%) of the reported crime occurrences, making it a high-crime area (hotspot) and the most affected neighborhood. Drug addiction (mean = 4.1940), poverty (mean = 3.9891), and negative peer influence (mean = 3.8087) were identified as key drivers of crime. It is therefore recommended that spatially responsive crime prevention strategies that focus on socioeconomic empowerment for youths, urban surveillance, community policing, and neighborhood-specific interventions to mitigate crime effectively should be given urgent attention.